Teaching efl academic writing in colombia: reflections in contrastive rhetoric (2011)
This essay relates observations to the reasons that advanced students of English as a foreign language in Colombia struggle with English composition. It identifies some cultural, academic, and disciplinary influences that may obfuscate their assimilation of the conventions of written English. It concludes by proposing that the teaching of context awareness would help said students in their writing of academic texts in English.Este ensayo relata observaciones acerca de las causas por las cuales los estudiantes de nivel avanzado de inglés como lengua extranjera tienen dificultades al redactar en dicha lengua. El ensayo señala algunas causas culturales, académicas y otras relacionadas con el campo específico de estudio, que podrían obstaculizar la asimilación de las normas del inglés escrito. Finalmente, propone que la enseñanza del reconocimiento de contexto les ayudaría a estos estudiantes a redactar textos académicos en inglés.